Total Phenolic Content and Antioxidant Activity of Anthocyanin Extract from Purple Yam (Dioscorea alata L.) Flour Using Different Solvents - Tamaroh, Siti; Raharjo, Sri; Murdiati, Agnes; Anggrahini, Sri (Pakistan Journal of Nutrition, 2018)
Background and Objective: Purple yam (Dioscorea alata L.) is a potential source of natural antioxidants due to its relatively high anthocyanin content. Anthocyanin is a natural source of antioxidants, acting as a free radical scavenger with a role in aging, cancer and degenerative illness prevention. Using a variety of solvents and acids, this study aimed to extract purple yam flour anthocyanins with high antioxidant activities. Methodology: Anthocyanins were extracted using methanol and ethanol-based solvents that were acidified with hydrochloric acid (HCl), citric acid or tartaric acid. The resulting extracts were assayed for anthocyanin and total phenolic contents, antioxidant activity (expressed as % radical-scavenger activity [%RSA]) and ferric reducing antioxidant power (FRAP). All data were analyzed using one-way analysis of variance. The differences were analyzed using Duncan’s multiple range test. The p